2016
DOI: 10.1016/j.cegh.2016.08.011
|View full text |Cite
|
Sign up to set email alerts
|

Malnutrition and anaemia associated with hypoxia among hospitalized children with community-acquired pneumonia in North India

Abstract: c l i n i c a l e p i d e m i o l o g y a n d g l o b a l h e a l t h 4

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 11 publications
0
7
0
1
Order By: Relevance
“…In our study, additional clinical features of pallor and wheezing were significantly associated with presence of hypoxic pneumonia. Pallor was also found to be significantly associated with hypoxic pneumonia in a study conducted in India (12) and also in a Nigerian study (41). Therefore, pallor must be included as an additional general danger sign of pneumonia.…”
Section: Discussionmentioning
confidence: 94%
See 2 more Smart Citations
“…In our study, additional clinical features of pallor and wheezing were significantly associated with presence of hypoxic pneumonia. Pallor was also found to be significantly associated with hypoxic pneumonia in a study conducted in India (12) and also in a Nigerian study (41). Therefore, pallor must be included as an additional general danger sign of pneumonia.…”
Section: Discussionmentioning
confidence: 94%
“…The Pneumonia Etiology Research for Child Health (PERCH) study, conducted in 7 countries to assess the etiology of and risk factors for severe and very severe pneumonia in children (1-59 months), reported the overall prevalence of hypoxia to be 35.8% (1,423/3,981) and 42.3% (748/1,769) among children with abnormal CXRs (28). Another observational study from India (12) conducted in a similar setting found hypoxia in 40% (54/135) of the patients, and of them, 37% (20/54) had pneumonia with lower chest indrawing and 63% (34/54) had severe pneumonia (12). Studies conducted in Nepal (24), Nigeria (25), and Sudan ( 26) have reported prevalence of hypoxemia to be 38.7, 41.5, and 42.7%, respectively, which is similar to that found by us.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Hal ini mirip dengan penelitian yang dilakukan oleh Nemani dan Awasthi, bahwa anemia ringan (Hb 10-10,9 g/dl) tidak berhubungan dengan derajat keparahan pneumonia (OR 0,74; IK 0,205-2,704), namun anemia sedang (Hb 7-9,9 g/dl) dan anemia berat (Hb <7 g/ dl) dibuktikan mempengaruhi kegagalan respons terapi antibiotik empirik, berturut-turut (OR 3,89; IK 1,27-11,89) dan (OR 8,5; IK 1,8-39,23). 10 Penelitian kami tidak membagi derajat anemia. Penelitian ini mendapatkan gambaran efusi pleura sebagai faktor risiko kegagalan terapi antibiotika empirik.…”
Section: Diskusiunclassified
“…Mechanisms underlying and influencing progression from pneumonia to severe pneumonia or complications are not clearly understood. It is reported that co‐morbid conditions like malnutrition, anaemia, and hypoxemia increase the risk of CAP‐associated mortality . In addition, there are several studies suggesting that genetic factors result in exaggerated and persistent inflammatory response in certain cases leading to adverse AO of CAP .…”
Section: Introductionmentioning
confidence: 99%